Mengoptimalkan Kinerja Perusahaan Melalui Tes dan Seleksi Karyawan Yang Akurat - Sekar Aulia Inaya; Putri Mukminah Izzatul Jannah; Winda Sri Rahayu; Aditya Maulana Yusuf; Mochammad Isa Anshori (Universitas Kristen Indonesia Toraja, 2024)
This research examines the importance of human resource management (HR) in achieving organizational goals, highlighting that the success of a company depends not only on technology and operational funds, but also on the quality of human resources. Employee performance, which includes quantitative and qualitative achievements of assigned tasks, is greatly influenced by the recruitment, training and potential development processes. The validity and reliability of performance measurement tools and appropriate selection are the keys to obtaining quality employees. The study also outlines the different types of tests used in the selection process, including cognitive, physical, personality, and achievement tests, as well as the importance of background investigations to ensure a candidate's suitability. Ethical and legal considerations in employee testing are also discussed to ensure fairness and privacy. Through good HR management, companies can increase their productivity and competitiveness in the global market.